2020
DOI: 10.3390/cli8100114
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Vegetation Cover at South Port Sudan Area

Abstract: Arid regions worldwide, for example, Sudan, are affected by climate change and susceptible to environmental deterioration. In this study, temperature and rainfall data from 1985 to 2015 obtained from the Sudan Meteorological Authority were compared with satellite images of vegetation coverage in southern Port Sudan. The objective of this study was to determine the impact of climate change on the vegetation cover in this area. Results showed significant increases in the annual maximum, minimum and average tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…Our results showed that there is an increasing trend of annual temperature over the last 35 years. These results agree with the findings of Loh et al [48], who reported an increase in mean annual temperature trend by 0.06 • C per year for the period between 1985-2015 in the Eastern part of Sudan. A similar trend was also reported for semi-arid regions of Iran where Tmin and Tmax increased over the last 50 years [49].…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that there is an increasing trend of annual temperature over the last 35 years. These results agree with the findings of Loh et al [48], who reported an increase in mean annual temperature trend by 0.06 • C per year for the period between 1985-2015 in the Eastern part of Sudan. A similar trend was also reported for semi-arid regions of Iran where Tmin and Tmax increased over the last 50 years [49].…”
Section: Discussionsupporting
confidence: 93%
“…The increasing energy demand on a global scale and, at the same time, the introduced restrictions on emissions harmful to the environment and the climate are prompting the search for non-conventional energy sources, including renewable energy sources [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Reanalysis datasets show that the global semi-arid and arid regions show a significant warming and drying trend, but there are obvious regional differences in precipitation changes [6]. Specifically, precipitation in southern Asia, southern Africa, and the northeastern part of the drylands of North America have increased significantly, while precipitation in central North America, southwestern South America, eastern Africa and western Asia have decreased significantly [7][8][9]. Based on the above research, we found that the research on climate change in arid regions is mainly focused on large-scale areas, but there is less attention to climate change in different ecological systems and different altitude gradients in arid regions.…”
Section: Introductionmentioning
confidence: 99%